THE ROLE OF NAPPE TECTONICS IN THE DEVELOPMENT OF ABNORMALLY HIGH FORMATION PRESSURE AND ECONOMIC METALLIFEROUS BRINES: A CASE STUDY OF THE SOUTHERN SIBERIAN CRATON - Vakhromeev A.G.; Sizykh V.I. (My University, 2006)
Worldwide experience in the exploration of oil-and-gas (hereafter, petroleum) fields shows that drilling deep wells in thick saliferous caprock above the petroleum pools often becomes problematic, or even becomes impossible, due to high-pressure spouts generated by abnormally high formation pressure (AHFP) of fluids [1] that develops in virtually all large petroliferous basins. At the Siberian Craton, the AHFP phenomenon has received too little attention, although considerable hydrocarbon and hydromineral resources of Russia are located in this region.